2009
DOI: 10.2746/042516409x452134
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiography and ultrasonography for the diagnosis of osteochondritis dissecans in the equine femoropatellar joint

Abstract: Reasons for performing study: Osteochondritis dissecans (OCD)lesions of the femoropatellar (FP) joint are diagnosed routinely by radiography, but lesions located in the trochlear groove or without accompanying subchondral bone changes can be difficult to visualise. Ultrasonography allows evaluation of articular cartilage and subchondral bone in the FP joint. Objectives:To document the radiographic and ultrasonographic appearance of OCD lesions in the equine FP joint, grade ultrasonographic lesions and compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 9 publications
3
31
1
2
Order By: Relevance
“…Our findings also supported previous studies, in that we identified a higher sensitivity of ultrasound in evaluating osteochondrosis lesions of the femoropatellar joint. 9 There was better agreement between radiographic operators vs. ultrasonographers only for detecting lateral trochlear ridge lesions us- ing the LM view. Ultrasonography had a better agreement between operators than radiography for detecting lateral and medial trochlear ridge lesions when the Ca60 • L-CrMO view was used.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Our findings also supported previous studies, in that we identified a higher sensitivity of ultrasound in evaluating osteochondrosis lesions of the femoropatellar joint. 9 There was better agreement between radiographic operators vs. ultrasonographers only for detecting lateral trochlear ridge lesions us- ing the LM view. Ultrasonography had a better agreement between operators than radiography for detecting lateral and medial trochlear ridge lesions when the Ca60 • L-CrMO view was used.…”
Section: Discussionmentioning
confidence: 95%
“…A site was considered positive for a lesion when fragmentation and/or a subchondral bone defect were present. The severity of the lesion was graded using a four-point system, based on criteria previously reported in dogs, 15 and horses, 9 where 0 = no lesion, 1 = cartilage irregularity with a visible superficial echogenic articular surface that shows concave deviation but is contiguous, 2 = a hyperechoic subchondral bone surface with moderate irregularity and discontinuity, and 3 = complete disruption of the echogenic articular surface and a hyperechoic subchondral bone with severe irregularity and discontinuity overlaid by heterogeneously echoic material. Only the results of the experienced operator were used for analyses of ultrasonographic sensitivity and specificity, and the ability of ultrasonography to predict severity of the lesions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…É possível avaliar, além do osso subcondral, demais estruturas articulares, como a linha de cartilagem articular, membrana sinovial, inserções de ligamentos e líquido sinovial. Em estudo que se comparou a radiografia com a ultrassonografia no diagnóstico de lesões osteocondrais na articulação femoropatelar, encontrou-se melhor sensibilidade e especificidade com o diagnóstico ultrassonográfico de lesões que se encontravam no terço final das trócleas medial e lateral do fêmur (BOURZAC et al, 2009).…”
Section: Diagnósticounclassified